Thoracic Paravertebral Block for Postoperative Pain Management in Percutaneous Nephrolithotomy Patients: A Randomized Controlled Clinical Trial - Ak, K. (Med Princ Pract, 2013)
OBJECTIVE: To investigate the effect of thoracic paravertebral block (PVB) on pain control and morphine consumption in percutaneous nephrolithotomy operations. SUBJECTS AND METHODS: This randomized controlled clinical study was performed on 60 American Society of Anesthesiologists (ASA) I-II patients between the ages of 18 and 60 years who underwent percutaneous nephrolithotomy with approval of the ethical committee and written consent of the patients. Patients were randomly allocated into two groups: group P had 4 ml of 0.5% levobupivacaine injected at each of the T10, T11, and T12 paravertebral spaces and a standard PVB, and group C received 4 ml of 0.9% NaCl solution. All patients were given standard general anesthesia. The follow-up of saturation, heart rate, peripheral oxygen, and blood pressure values was recorded before induction, intraoperatively, and postoperatively. At postoperative 1, 2, 6, 12, and 24 h, the visual analog scale (VAS), Ramsey sedation score, respiratory rate, and 24-hour total morphine consumption were recorded. In addition, side effects and satisfaction of patients were recorded. RESULTS: VAS scores and total morphine consumption were lower in group P than in group C: 2.3 vs. 4.3 and 22.3 vs. 43.2 mg, respectively (p < 0.05). The level of satisfaction was higher in group P than group C. Differences between groups in other parameters were not significant. CONCLUSIONS: Thoracic PVB with levobupivacaine provided a good postoperative analgesia and increased patient satisfaction for those who underwent percutaneous nephrolithotomy.